Perkembangan Psikososial Pada Masa Kanak Kanak Awal - Fauziah Nasution; Annisa Hasanah Nasution; Chadiza Auliana Utami; Muhammad Iqbal Ritonga (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This study aims to find out about early childhood development regarding psychosocial in children. This type of research is quantitative research using data collection conducted in natural conditions, sources and accurate data by conducting interviews and documentation to obtain data in the study. The results showed that the development of early childhood in terms of psychosocial development chronologically, early childhood is a period of development from the age of 1 or 2 years to 5 or 6 years. Biological development at this time is rapid, but sociologically he is still very much bound by his environment and family. Therefore, the functionalization of the family environment in this phase is very important to prepare children to enter the wider environment, especially the school environment. Childhood is often called the ethical period, the sensory period, and the period of opposing parents. It is called ethical because it is the time of the feeling of beauty. Children's social development is strongly influenced by the sociopsychological climate.